Market discipline and the regulatory change: evidence from Vietnam - Tu DQ Le (Cogent Economics & Finance, 2020)
Following the recent global financial crisis, Vietnamese banks experienced changes in the minimum capital adequacy requirement following the Basel framework. We examine the impact of the regulatory change on market discipline between 2006 and 2015. The findings show a weakening of market discipline when the minimum capital adequacy requirement of 9% is imposed. The same is true for foreign-owned commercial banks during the period of implementing new capital regulation. Also, there is no evidence of the difference in market discipline between bank ownership and risks in the Vietnamese banking system. Our research has implications for bank supervisors, policy-makers, and bank managers.
Keywords: G21; G28; G30; 330; market discipline; capital regulation; bank risk-taking; system GMM; Vietnam